A Comparative Pilot Survey of Kratom Utilization by Cancer and Non-Cancer Consumers - Jace Hubley; Saunjoo L. Yoon; Oliver Grundmann (Journal of Palliative Medicine, 2026)
Background: Kratom, an analgesic and mood-altering herbal product from Southeast Asia, has gained popularity and is used for self-treatment purposes in the United States. Objective: To evaluate the utilization of kratom by cancer patients compared to those without a cancer diagnosis. Methods: An anonymous online survey was distributed to evaluate demographic, primary beneficial, and detrimental effects relative to cancer diagnosis, quality of life, and kratom use patterns. The final sample included 136 respondents living in the United States who self-selected for the survey. Results: Respondents with a cancer diagnosis indicated different kratom use patterns and utilization for pain and mental health related to their cancer diagnosis. Cancer patients engaged with kratom relative to the diagnosis, while those without a cancer diagnosis used it for longer periods for other pre-existing health conditions. Conclusions: Kratom is used by cancer patients for diverse reasons. Further research is needed to generalize findings from this pilot survey.